PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR PAI MELALUI MODEL PEMBELAJARAN AKTIF DAN PENDEKATAN INTENSIF PADA SISWA KELAS IV SDN SUKAHARJA 03 KARAWANG - Larasati nur firzanah; Ilham Mukhtar Sya’bani; Muhajir A.M Al-Raji; M. Makbul (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT This study aimed to improve students’ participation and learning outcomes in Islamic Religious Education through the implementation of an interactive learning method in Grade IV of SDN Sukaharja 03 Karawang. The study was motivated by the low level of student engagement during the learning process, which contributed to unsatisfactory learning outcomes. The novelty of this study lies in the application of an interactive learning method that integrates discussion, group work, demonstrations, and learning quizzes to enhance both student participation and learning achievement in Islamic Religious Education at the elementary school level. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were Grade IV students of SDN Sukaharja 03 Karawang. Data were collected through observation, learning achievement tests, and documentation and were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the interactive learning method successfully increased students’ participation in asking and answering questions, engaging in discussions, and collaborating with peers during the learning process. Learning outcomes also improved, as indicated by the increase in the class average score from 70 in Cycle I to 81 in Cycle II, while the learning mastery rate increased from 44% to 97%. These findings indicate that the interactive learning method is effective in enhancing student participation and learning outcomes in Islamic Religious Education and can serve as an alternative instructional strategy to promote more active, participatory, and student-centered learning in elementary schools ABSTRAK Penelitian ini bertujuan untuk meningkatkan partisipasi dan hasil belajar siswa pada mata pelajaran Pendidikan Agama Islam melalui penerapan metode pembelajaran interaktif di kelas IV SDN Sukaharja 03 Karawang. Penelitian ini dilatarbelakangi oleh rendahnya keterlibatan siswa dalam proses pembelajaran yang berdampak pada rendahnya hasil belajar. Kebaruan penelitian terletak pada penerapan metode pembelajaran interaktif yang mengintegrasikan diskusi, kerja kelompok, demonstrasi, dan kuis pembelajaran untuk meningkatkan partisipasi serta hasil belajar siswa pada pembelajaran PAI di sekolah dasar. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing meliputi perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SDN Sukaharja 03 Karawang, dengan data dikumpulkan melalui observasi, tes hasil belajar, dan dokumentasi, kemudian dianalisis secara deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa metode pembelajaran interaktif mampu meningkatkan partisipasi siswa dalam bertanya, menjawab pertanyaan, berdiskusi, dan bekerja sama selama pembelajaran. Peningkatan hasil belajar ditunjukkan oleh kenaikan nilai rata-rata kelas dari 70 pada Siklus I menjadi 81 pada Siklus II, sedangkan persentase ketuntasan belajar meningkat dari 44% menjadi 97%. Temuan ini menunjukkan bahwa metode pembelajaran interaktif efektif dalam meningkatkan partisipasi dan hasil belajar Pendidikan Agama Islam serta dapat menjadi alternatif strategi pembelajaran yang lebih aktif, partisipatif, dan berpusat pada siswa di sekolah dasar.